A Syndemic Perspective on the Management of Non-communicable Diseases Amid the COVID-19 Pandemic in Low- and Middle-Income Countries - Yadav, Uday Narayan; Rayamajhee, Binod; Mistry, Sabuj Kanti; Parsekar, Shradha S.; Mishra, Shyam Kumar (Frontiers in Public Health, 2020)
The global pandemic of novel coronavirus disease (COVID-19) has largely impacted the lives of the people living with non-communicable diseases (PLWNCDs). The health of PLWNCDs worsen when syndemic epidemics occur as a result of the interaction between socioecological and biological interface, resulting into adverse outcomes. These interactions can affect physical, emotional, and social wellbeing of PLWNCDs, increases exposure to NCD risk factors and disrupts the essential public health service amid this widespread pandemic. In this paper, we argue the need for country-wise syndemic framework to deal with the impact of COVID-19 on the lives of PLWNCDs in low- and middle- income countries (LMICs).